2014
DOI: 10.1186/2041-9139-5-27
|View full text |Cite
|
Sign up to set email alerts
|

Heterochrony repolarized: a phylogenetic analysis of developmental timing in plethodontid salamanders

Abstract: BackgroundDisentangling evolutionary shifts in developmental timing (heterochony) is dependent upon accurate estimates of ancestral patterns. However, many classic assessments of heterochronic patterns predate robust phylogenetic hypotheses and methods for trait reconstruction, and therefore may have been polarized with untested ‘primitive’ conditions. Here we revisit the heterochronic modes of development that underlie the evolution of metamorphosis, maturation, and paedomorphosis in plethodontid salamanders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 72 publications
3
48
0
Order By: Relevance
“…In urodeles the increase in the genome allowed the transition from a biphasic life cycle to increasingly frequent cases of paedomorphosis or even to obliged neoteny [Gregory, 2002a[Gregory, , 2005. In plethodontids it was observed that the ancestral forms probably had a shorter larval period than current forms [Bonett et al, 2014], implying a co-evolution between genome increase and paedomorphosis/neoteny. The progressive development of paedomorphosis and neoteny characterizes also the evolution of the current lungfishes harboring very large genomes [Joss, 2006].…”
Section: Interaction Of Transposons and Genome Size With Evolutionarymentioning
confidence: 89%
“…In urodeles the increase in the genome allowed the transition from a biphasic life cycle to increasingly frequent cases of paedomorphosis or even to obliged neoteny [Gregory, 2002a[Gregory, , 2005. In plethodontids it was observed that the ancestral forms probably had a shorter larval period than current forms [Bonett et al, 2014], implying a co-evolution between genome increase and paedomorphosis/neoteny. The progressive development of paedomorphosis and neoteny characterizes also the evolution of the current lungfishes harboring very large genomes [Joss, 2006].…”
Section: Interaction Of Transposons and Genome Size With Evolutionarymentioning
confidence: 89%
“…Biphasic life cycles occur in three different clades (the subfamily Spelerpinae, Hemidactylium and some Desmognathus ). Several spelerpine lineages express obligate paedomorphosis (Bonett et al 2014a,b), but facultative paedomorphosis is uncommon. Direct-developing lineages collectively represent the greatest diversity of salamanders (Wake and Hanken 1996), and range from western North America into South America, with relict species in the Mediterranean and Asia (Dunn 1926; Wake 1966; Min et al 2005).…”
mentioning
confidence: 99%
“…Analyses based on molecular phylogenies have indicated that life-cycle evolution is reversible, however, with complex life cycles secondarily derived from direct-developing and paedomorphic ancestors (Titus and Larson 1996; Chippindale et al 2004; Mueller et al 2004; Bonett et al 2014a,b). With regard to direct development, there are either (1) multiple episodes of direct development from biphasic ancestors, or (2) re-evolution of free-living larvae from direct-developing ancestors, including the possibility that a direct-developing life cycle could be the ancestral life cycle for plethodontids (Chippindale et al 2004; Mueller et al 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is a serious problem for the Beachy-Bruce (1992) hypothesis that lunglessness is a rheotropic adaptation to larval life (an extension of the older idea: lungs would buoy the larvae into flowing water, causing them to be swept away). Desmognathus is deeply nested, not sister to all remaining plethodontids, and Bonett et al (2014) argued that direct development may well have been ancestral for Plethodontidae. Finally, based on arguments by and Shen et al (2016), plethodontids might have arisen in northwestern North America, not Appalachia, or it is at least as probable as Appalachia.…”
Section: How Did Karsenia End Up In Korea?mentioning
confidence: 99%